IN SILICO STUDY OF CENTELLA ASIATICA ACTIVE COMPOUND AS BACE1 INHIBITOR IN ALZHEIMER’S DISEASE - Mawaddani, Nala; Wibowo, Natalia RK; Nadhira, Qumaira HH; Pramifta, Ratih Ayu (JSMARTech, 2020)
Alzheimer (AD) is a chronical neurodegenerative disease which is the 6th leading cause of death worldwide. About 36 million cases in the world and may increase to 115 million in 2050. The pathological cause of AD is the presence of residual A? peptides. A? peptides is produced in the cleavage process of the amyloid precursor protein (APP) sequentially by Beta amyloid precursor protein cleavage enzyme 1 (BACE1) and ?-secretase. Flavonol, germacrene B, and sitosterol are compounds found in Centella asiatica which is has potential as BACE1 inhibitor. The aim of this study was to analyze the interaction between BACE1 with flavonol, germacrene B and sitosterol by molecular docking to predict the BACE1 inhibitor potent of those compound. We obtained BACE1 from RSCB database, flavonol, germacrene B and sitosterol from PubChem database. Molecular dockcing was done using Hex 8.0.0. The docking result were vizualized with Discovery Studio 3.5. Interaction of BACE1 resulted binding energy for sitosterol was-239,7 kcal/mol, flavonol was -188,1 kcal/mol, and germacrene B was -185,6 kcal/mol. Flavonol and sitosterol bound to the active site of BACE1 involving Thr232 and Ile110 on flavonol, while Tyr71 on sitosterol. All of the active compounds didn?t have the interaction at S1? subsite,which is the center of BACE1 active site which has become the key of APP activation from BACE1. This study has shown that flavonol and sitosterol had potential to reduce BACE1 activity but not directly inhibit BACE1 activity.